Implementasi Salus Populi Suprema Lex di Tengah Karut-Marut Kebijakan PPKM di Indonesia - Aini Shalihah (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
The Covid-19 pandemic has hit Indonesia since the beginning of 2020 until now which has shattered the joints of people's lives, including the economic and other sectors. This is certainly a challenge for the government to deal with the pace of Covid-19. So far, the government has issued various regulatory policies starting from the PSBB, New Normal, Micro PPKM, Emergency PPKM, PPKM Level 1-4, and most recently PPKM Nataru. Since PPKM was enacted, it was considered a solution for the government to be able to cope with the pandemic, with the aim of people's safety being the highest law. The government considers that PPKM is a form of salus populi suprema lex. This is why the government needs to issue policies related to PPKM regulations. With the hope that all elements of society can comply with these rules in order to reduce the number of active spreads. However, with the government always revising the rules related to PPKM policies, it invites problems. This is considered by the government to be less ready to formulate regulatory policies related to PPKM. Besides the government is considered immature in making policies regarding the existence of PPKM regulations, its implementation is still chaotic and far from the principle of salus populi suprema lex expected by the government. This then needs to be discussed further in relation to the application of the principle of salus populi suprema lex amidst the chaotic PPKM policies during the pandemic. This paper aims to find out related to the implementation of the principle of salus populi suprema lex which is claimed to be the most solutive solution during a pandemic through the PPKM policy issued by the government. This study uses a normative juridical approach and empirical juridical approach and analyzed using the descriptive analysis method. The results of this study indicate that in realizing the implementation of the Salus Populi Suprema Lex in dealing with the rate of Covid-19, apart from the government being responsible for protecting the people and the important role of the community, it is also a vital element in the success of policies and regulations issued by the central/regional government related to handling Covid-19 as well as PPKM.Keywords: Implementation; Salus populi suprema lex; Politic; PPKM;